1995
DOI: 10.1051/animres:19950204
|View full text |Cite
|
Sign up to set email alerts
|

Level and quality of protein in rations for lactating ewes

Abstract: Summary — The effect of 2 levels of crude protein in the ration (110 and 90% of theoretical requirements) and of 3 main protein sources in the concentrate (faba beans, soybean cake and fish meal) on changes in live weight and body condition score, milk production, plasma concentration of non-esterified fatty acids and urea, and lamb growth was studied in 36 lactating Rasa Aragonesa ewes rearing 2 lambs submitted to an energy restriction level of 30% of their theoretical requirements. The average decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Sainfoin grazing during lactation was compared with 2 systems that have proven to yield good ADG of lambs in an autochthonous breed specialized in lamb production with low milk production (around 1 kg/d; Jaime and Purroy, 1995). Suckling lambs that grazed sainfoin had similar BW and age at weaning to their counterparts, which suggests that the intake of standard milk was similar among strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Sainfoin grazing during lactation was compared with 2 systems that have proven to yield good ADG of lambs in an autochthonous breed specialized in lamb production with low milk production (around 1 kg/d; Jaime and Purroy, 1995). Suckling lambs that grazed sainfoin had similar BW and age at weaning to their counterparts, which suggests that the intake of standard milk was similar among strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the ewes in the present study were fed at a similar level to those of the previous study only for the first 21 d of lactation may explain why they lost weight compared with the ewes that were fed during the entire 63-d lactation. Jaime and Purroy (1995) reported that ewes provided with 110% of CP requirements during lactation produced more milk than ewes receiving 90% of CP requirements. The ewes in the present study were fed to receive 150% of their nutritional requirements based on the data of Kawas and Huston (1990), but there was only a difference in milk production between FEED and CONTROL ewes during the dry season.…”
Section: Discussionmentioning
confidence: 99%
“…This loss is even greater, exceeding 150 g per d, when fatter ewes are subject to undernutrition [34]. This general phenomenon has been observed in thintailed ewes, where BW losses in lactation are positively related (r = + 0.58; P < 0.001) to the BW at lambing in Aragonesa ewes [31].…”
Section: Lactation and The Suckling Lambmentioning
confidence: 93%